2020
DOI: 10.1097/md.0000000000020471
|View full text |Cite
|
Sign up to set email alerts
|

Tongue diagnosis indices for gastroesophageal reflux disease

Abstract: Traditional Chinese medicine tongue diagnosis can mirror the status of the internal organ, but evidence is lacking regarding the accuracy of tongue diagnosis to gastroesophageal reflux disease (GERD). This study was to investigate the association between GERD and tongue manifestation, and whether tongue imaging could be initial diagnosis of GERD noninvasively. We conducted a cross-sectional, case-controlled observational study at Kaohsiung Chang Gung Memorial Hospital in Taiwan from January 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…[44,45] The value of the TCTD diagnostic method is evident in diagnosing a variety of diseases, including breast cancer, gastrointestinal disorders, COVID-19, and diabetes. [17,[44][45][46][47] For instance, the proportion of greasy coatings was higher in patients with critical COVID-19 pneumonia compared patients with mild, moderate, and severe COVID-19 pneumonia. [44] The amount and thickness of tongue coatings in the spleen-stomach area are related to the severity of gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44,45] The value of the TCTD diagnostic method is evident in diagnosing a variety of diseases, including breast cancer, gastrointestinal disorders, COVID-19, and diabetes. [17,[44][45][46][47] For instance, the proportion of greasy coatings was higher in patients with critical COVID-19 pneumonia compared patients with mild, moderate, and severe COVID-19 pneumonia. [44] The amount and thickness of tongue coatings in the spleen-stomach area are related to the severity of gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tongue diagnosis is an indispensable part of TCM diagnosis and can reflect the severity and development of diseases. [44,45] The value of the TCTD diagnostic method is evident in diagnosing a variety of diseases, including breast cancer, gastrointestinal disorders, COVID-19, and diabetes. [17,[44][45][46][47] For instance, the proportion of greasy coatings was higher in patients with critical COVID-19 pneumonia compared patients with mild, moderate, and severe COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…According to the TCM tongue diagnosis theory, the normal thickness of tongue fur should be thin and uniform, while very thick or very thin (or absent) tongue fur may indicate some diseases or prediseases in the body [ 23 ]. Correspondingly, modern research has observed that gastroesophageal reflux disease and type 2 diabetes patients tend to have thick tongue fur [ 24 , 25 ], while primary dysmenorrhea patients tend to have less tongue fur [ 26 ]. From the perspective of tumor markers, our results also suggest that people with thick tongue fur or peeling or less tongue fur are more likely to have health issues.…”
Section: Discussionmentioning
confidence: 99%
“…The human tongue is an essential organ of the body and can provide much information on human health status [1,2]. Tongue diagnosis is a simple and noninvasive technique for the syndrome differentiation and treatment in traditional Chinese medicine (TCM) [3][4][5][6][7]. Sublingual varices are a symbol of TCM judgments of blood stasis.…”
Section: Introductionmentioning
confidence: 99%